(3TQM YeOI GdSGdcs - (3TeS GdOjf eMeO Hf YHO GdfYe GdLhLQi GdTGaYjs; (3GHf GdfbjHs ((3MjOQ CHGO s)
(3ChdgG (B:s
(3HGH GdTQcI , HcSQ GdTje hSchQ GdQGA jbGd CjVkG HaJM GdTjf hcSQ GdQGA gi dZI GdENJdGW hGdEeJRGL s
(3BNQgG (B:s
(3CeG YjhH GdhLg hGdcajf ef GdfSGA aEfg dGjbH ajgG ZdG GdQLGd hbO JbOe R bO ESJQGM Gdbde HJMQjQ GdeLdO GdKGfi ef GdcJGH GdeSJWGH GdeYQha HTQM GdYeOI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI CNQis
(3Yf fSNI cJHJ ai GdHUQI s
(3cJH eJf GdYeOI HGdMeQIYdjgG JYdjbGJ hJUMjMGJ s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdTGaYjs